Management of Education Utilizing Technology for Schools in Southeast Asia - Aprianto, Iwan; Mahdayeni, Mahdayeni; Herliani, Pakinah; Iswanto, Iswanto; Gelileo, Mia Angela (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2023)
This research will examine and comprehend the function and impact of technology usage in the context of education management in Southeast Asian schools. In the rapidly evolving digital and information technology era, education in the region faces many obstacles and opportunities. This research employs a qualitative literature review methodology to comprehend how schools in Southeast Asia use and manage technology in educational contexts. Data collection requires searching for, selecting, and analyzing relevant literature based on topic accuracy, relevance, reliability, and quality standards. Data analysis entails identifying central themes, methods utilized in the literature, and pertinent findings. The findings indicate that education resource management is essential for enhancing the quality of education in Southeast Asia. Faced with obstacles such as unequal access to education, varying quality of education, and policy shifts, the efficient management and application of technology have emerged as a viable solution. The equitable distribution of educational resources such as facilities, teachers, and learning materials among schools in different regions ensures that every student has access to a quality education.